A 200MHz analogue-ROM based direct digital frequency synthesiser with amplitude modulation - Shah, S; Collins, S; IEEE; IEEE (2001)
A novel, low power frequency synthesiser system with 60MHz output bandwidth is reported which is suitable for integration in a single chip RF transceiver. The system is based upon a conventional DDFS architecture. However, the problems which usually arise from the non-ideal-behaviour of the DAC and the high power consumption of a ROM are avoided by using a non-volatile analogue memory array. Simulation results are presented which show that the system is suitable for use in an RF transceiver.